(3GdJPcQI GdaGNQI aj abg GdYJQI GdWGgQIs - (3GdMSf Hf eMeO TQa GdOjf GdfMhjs
(3ChdgG (B:s
(3cJGH GdWgGQI fOH dbGVi GdMGLI Cf jHYO hjSJJQ Yf GdfGS s
(3BNQgG (B:s
(3Gddge EfaYfG jG cQje HeG YdeJfG hCfTQ YdjfG SJQc , Efc SejY GdOYGA s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda SfI (B796s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdgOhjI (B217) s
Keywords: (3abg GdePGgH GdCNQis